Slovenia: National Regulations in the Shadow of a Common Past - Kotnik , Maja; Šepec, Miha (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
For many years, until the country’s independence, Slovenian criminal law developed under the influence of communism. With the new modern Constitution of the Republic of Slovenia, it was necessary for the country to establish its own modern criminal law, which would no longer be tied to past communist patterns. Accordingly, both criminal procedural law and criminal substantive law have been revised. New Slovenian criminal law is based on the general principles, such as the principle of legitimacy and restricted repression in connection with the rule of law, the principle of humanity, the principle of individualization of criminal sanctions, the principle of legality, the principle of fairness of procedure, the principle of formality, the principle of material truth, the debate principal, the principle of free judgement of evidence, the principle of subjective or guilty responsibility, the principle in dubio pro reo, and finally, the assumption of innocence. In addition to these principles, Slovenian criminal law also rests on the general concept of criminal offense, which is formed by three key elements, namely the fulfillment of the nature of the offense, illegality, and guilt. All of the above represent the key pillars of Slovenian criminal law, making it fair, modern, and comparable to other criminal systems in European countries.KEYWORDS: Slovenia, historical overview, criminal legislation, criminal law, practice of criminal justice